Overcoming terms of service: a proposal for ethical distributed research. Issue 11 (19th September 2019) - Halavais, Alexander
ABSTRACT: The last two years has marked a turning point in access to large-scale social media data for many researchers, as platforms hobbled their APIs and made recording, archiving, and analyzing social life online far more difficult. Particularly in the context of the United States, where violating the rules put in place by social platforms has the potential to lead to criminal charges, the balance of power between the extremely financially successful social media industry on one side, and the users and researchers of these platforms on the other, has become dangerously skewed. This article argues for a pragmatic partnering with the users to do research, rather than with the platform owners, and suggests some ways in which this might be accomplished.